Deficiency of Ninjurin1 attenuates LPS/D‐galactosamine‐induced acute liver failure by reducing TNF‐α‐induced apoptosis in hepatocytes. Issue 20 (7th September 2022) - Kim, Min Woo; Kang, Ju‐Hee; Jung, Hyun Jin; Park, Se Yong; Hwang, Jong‐Ik; Seong, Je Kyung; Yoon, Yeo Sung; Oh, Seung Hyun
Abstract: Nerve injury‐induced protein 1 (Ninjurin1, Ninj1) is a membrane protein that mediates cell adhesion. The role of Ninj1 during inflammatory response has been widely investigated in macrophages and endothelial cells. Ninj1 is expressed in various tissues, and the liver also expresses high levels of Ninj1. Although the hepatic upregulation of Ninj1 has been reported in human hepatocellular carcinoma and septic mice, little is known of its function during the pathogenesis of liver diseases. In the present study, the role of Ninj1 in liver inflammation was explored using lipopolysaccharide (LPS)/D‐galactosamine (D‐gal)‐induced acute liver failure (ALF) model. When treated with LPS/D‐gal, conventional Ninj1 knock‐out (KO) mice exhibited a mild inflammatory phenotype as compared with wild‐type (WT) mice. Unexpectedly, myeloid‐specific Ninj1 KO mice showed no attenuation of LPS/D‐gal‐induced liver injury. Whereas, Ninj1 KO primary hepatocytes were relatively insensitive to TNF‐α‐induced caspase activation as compared with WT primary hepatocytes. Also, Ninj1 knock‐down in L929 and AML12 cells and Ninj1 KO in HepG2 cells ameliorated TNF‐α‐mediated apoptosis. Consistent with in vitro results, hepatocyte‐specific ablation of Ninj1 in mice alleviated LPS/D‐gal‐induced ALF. Summarizing, our in vivo and in vitro studies show that lack of Ninj1 in hepatocytes diminishes LPS/D‐gal‐induced ALF by alleviating TNF‐α/TNFR1‐induced cell death.